Production of lysozyme nanofibers using deep eutectic solvent aqueous solutions - Silva, Nuno H. C. S.
Amyloid fibrils have recently gained a lot of attention due to their morphology, functionality and mechanical strength, allowing for their application in nanofiber-based materials, biosensors, bioactive membranes and tissue engineering scaffolds. The in vitro production of amyloid fibrils is still a slow process, thus hampering the massive production of nanofibers and its consequent use. This work presents a new and faster (2-3 h) fibrillation method for hen egg white lysozyme (HEWL) using a deep eutectic solvent based on cholinium chloride and acetic acid. Nanofibers with dimensions of 0.5-1 mu m in length and 0.02-0.1 mu m in thickness were obtained. Experimental variables such as temperature and pH were also studied, unveiling their influence in fibrillation time and nanofibers morphology. These results open a new scope for protein fibrillation into nanofibers with applications ranging from medicine to soft matter and nanotechnology. (C) 2016 Elsevier B.V. All rights reserved.